Capacity control/modulation of a refrigeration compressor - Sng, Han Yang. (2013)
Refrigeration and air-conditioning are widely-used applications in modern day society to cool products and ventilate buildings. Many air-conditioning and refrigeration systems are designed to maintain a fixed amount of cooling capacity. In practice, loads exhibit wide ranges of variation depending on operating conditions such as weather and amount of insulation. To reduce the energy consumption, it is desirable to incorporate capacity control modules into these cooling systems.